The entrepreneurship ecosystem in the ICT sector in Qatar: local advantages and constraints. Issue 2 (8th March 2020) - Ben Hassen, Tarek
Abstract : Purpose: The purpose of this paper is to analyze the characteristics and dynamics of the entrepreneurship ecosystem in the ICT sector in Qatar. Design/methodology/approach: The methodology of this research is based on a literature review and information collected through semistructured interviews with the different stakeholders involved in the entrepreneurship ecosystem in the ICT sector in Qatar. Findings: The results show that two opposite forces shape the entrepreneurship ecosystem in the ICT sector in Qatar. On one hand, the strong determination and intervention of the Qatari government to diversify the economy by creating a vibrant ecosystem in the ICT sector. On the other hand, entrepreneurs in this sector are still facing some barriers and difficulties, and those issues are tightly related to Qatar's economic characteristics as a rentier state whose economy is driven by hydrocarbon resources. Originality/value: These findings contribute to the clarification and critical analysis of the current dynamics of the entrepreneurship ecosystem in the ICT sector in Qatar, which would have several policy implications.